Análisis de publicaciones en promoción de la salud: una mirada a las tendencias relacionadas con prevención de la enfermedad (2015)
ABSTRACT: We carried out a qualitative documental research in order to have a closer look at the current state of the discussion on health promotion in Colombia; our research analyzed the contents of articles published in indexed journals between the years 2000 and 2010. The purpose was to know the tendencies and contributions to the discussion on health promotion (ps). One of the relevant categories was the relationship between health promotion-disease prevention (pe), in which we can see tendencies such as: assuming both as unified concepts; ps and pe as different concepts; and problematization in practice of ps in, present in the discussion with insurance, interdisciplinarity, and ‘intersectoriality’, and the blurry borders between ps and pe. We raise the need for approaches that go beyond the dichotomic and disciplinary view, as well as recognition in everyday scenarios the places where ps is learnt and realized.